284. Evaluation of Oral Step-Down Therapy for Enterobacteriaceae Bloodstream Infection. (31st December 2020) - Utley, Sara; Bouknight, Dawn; Patel, Radha; Stock, Kent
Abstract: Background: Oral antibiotic stepdown therapy for Gram-negative (GN) bloodstream infection (BSI) appears to be a safe option, though high bioavailability drugs like fluoroquinolones (FQ) and trimethoprim-sulfamethoxazole are often recommended without clear evidence demonstrating superiority. Due to increasing concerns of FQ resistance and collateral damage with an increasing community C. difficile rate, our organization sought to reduce overall FQ use and a shift toward oral beta-lactams (BL) was observed. A review was conducted to assess the outcomes of this shift. Methods: This retrospective cohort included all patients within our 3-hospital system who had a positive GN blood culture and were transitioned to oral therapy to complete treatment outpatient for bacteremia between Jan 2017-Sept 2019. The primary outcome was recurrent BSI within 30 days of completing initial treatment. Secondary outcomes included 30-day mortality, 30-day recurrence of organism at an alternate source, 30-day readmission, and 90-day BSI relapse. Results: Of 191 GN BSIs, 77 patients were transitioned to oral therapy. The mean age was 68 years, 60% were female. The most common source of infection was described as urine (39/77), intra-abdominal (16/77), unknown (13/77). Mean total antibiotic duration (IV plus PO) was 14 days (range 7–33). Patients received an average of 5 days IV prior to transitioning to PO therapy. The most common PO class was a 1 st gen cephalosporin (29/77), followed by BL/BL inhibitor (16/77), and a FQ (13/77). There were no 30-day relapse BSIs observed in this cohort. There was 1 patient discharged to inpatient hospice, and no other 30-day mortality observed. There were 4 recurrent UTIs observed within 30 days, none of which required readmission. Of the twelve 30-day readmissions, 1 was considered by the investigators to be related to the initial infection. Conclusion: An opportunity for education regarding duration of therapy was identified. Oral beta lactam use in our limited population appears to be a reasonable option to facilitate discharge. Results should be confirmed in additional, larger studies. Disclosures: All Authors : No reported disclosures